[PP.11.01] AORTIC PULSE WAVE VELOCITY IS RELATED TO CORONARY HEART DISEASE IN WOMEN BUT NOT IN MEN. (September 2016) - Hametner, B.; Parragh, S.; Mayer, C.; Whitelegg, K.; Weber, T.; Wassertheurer, S.
Abstract : Objective: Moderate age-dependent differences in aortic pulse wave velocity (PWV) between females and males have been reported previously. Nevertheless, studies on gender-specific interactions of PWV and cardiovascular diseases are lacking. Therefore, the aim of this study is to investigate age-dependent sex differences in PWV in relation to coronary heart disease (CHD). Design and method: A total of 645 patients from 60 to 79 years with suspected CHD underwent coronary angiography at the hospital in Wels-Grieskirchen (Austria). Invasive aortic PWV was measured in all patients by catheter pullback. According to the indication of the angiography, patients were divided into four groups (male/female, CHD/noCHD). As PWV strongly depends on age, patients were divided in two decades of life for further statistical analysis (60–69 years, 70–79 years). For both sexes, groups with and without CHD were compared. To minimize the influence of blood pressure, in a second step PWV was corrected for invasive aortic systolic blood pressure (aoSBP) by linear regression. Results: For each decade and each group, values of aoSBP, PWV and corrected PWV (corrPWV) can be found in the table. In both decades, differences in PWV between CHD and noCHD were not significant in males (p > 0.1), whereas differences were significant in females (p < 0.01). While aoSBP was significantly higher for patients with CHD in both sexes in decade 60–69 (p < 0.05), no significant differences could be found for patients aged 70–79 (p > 0.1). After accounting for unequal pressure levels, for females the differences in corrPWV between CHD and noCHD were still significant (p < 0.05), while they remained not statistically significant for males (p > 0.1). Conclusions: In patients with suspected coronary heart disease, pulse wave velocity is related to CHD in women but not in men. Blood pressure differences could not explain these results, as the effects remained when PWV was corrected for aortic systolic blood pressure. This finding indicates that a sex-dependent interplay between arterial stiffness and CHD is present which needs future attention. Figure. No caption available.